Using case study methodology to approach the views of teachers of english on classroom disciplinary strategies (2012)
This qualitative study aims at identifying the disciplinary strategies claimed to be used by a group of five secondary classroom teachers of English in public or semi-public schools in Chile. To conduct this research, a semi-structured interview was applied to participants. The data were analyzed using the principles of semantic content analysis and the grounded theory technique in order to organize the categories and subcategories from the data. The results show that some of the teachers declare using a rising tone of voice, scolding and expelling difficult students from the classroom as key disciplinary techniques; other teachers claim that disciplinary strategies help them to accomplish the teaching aim in a lesson. Este estudio cualitativo tiene como objetivo identificar las estrategias disciplinarias que declara usar un grupo de cinco profesores de inglés como lengua extranjera, de la enseñanza secundaria, que laboran en la educación pública o semipública en Chile. El estudio se basó en una entrevista semiestructurada, cuyos datos se interpretaron a partir de los principios del análisis del contenido semántico y la técnica de la teoría fundamentada. Luego se organizaron en categorías y subcategorías. Los resultados muestran que la mayoría de los informantes declara aumentar el tono de su voz o emplear la reprensión y la expulsión del aula como técnicas para mantener la disciplina. Otros expresan que las estrategias de disciplina les ayudan a alcanzar el objetivo de la clase.